Factors affecting real property gains tax compliance intention among individuals - Noriza, Othman (2023)
Not returning the CKHT 1A Form after a transaction of selling or disposing properties as required by the Inland Revenue Board of Malaysia (IRBM) through Real Property Gains Tax (RPGT) Act shows that there is a tax non-compliance among disposers. This study investigated the factors affecting RPGT compliance intention among individuals. A theoretical framework was developed based on the Theory of Planned Behaviour. The objectives of the study were to determine the level of attitude, subjective norms, tax education, tax awareness and RPGT compliance intention among individuals; and the relationship between attitude, subjective norms, perceived behavioural control (tax education and tax awareness) and RPGT compliance intention among individual disposers. Attitude had the highest mean value followed by subjective norm and tax awareness. The level of tax education had the lowest mean value, indicating that it is moderate. By employing a random sampling method, a total of 186 responses were gathered from online questionnaires. The results of multiple regression analysis showed that attitude and subjective norm positively influenced the intention towards RPGT compliance while tax awareness influenced adversely. The findings also revealed that the independent variables tested explained 43.5% of the variance in RPGT compliance intention. Hence, the model used in this study was supported as suitable and was able to predict the dependent variable, RPGT compliance intention. These results offer IRBM with empirical support for the formulation of more effective measures to increase RPGT compliance in Malaysia. This study has certain limitations such as small sample size and the exclusive focus on TPB model elements that may not adequately explain RPGT compliance behaviour. Future studies should employ a greater number of participants to ensure that the findings are applicable and beneficial for all Malaysian taxpayers and should incorporate different theoretical models and moderating and mediating factors to better comprehend the mechanisms behind RPGT compliance behaviour.